2021
DOI: 10.3892/mmr.2021.11891
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of steroid hormones in three different preeclamptic models

Abstract: Preeclampsia (PE) is a complication of pregnancy and is characterized by hypertension and proteinuria, threatening both the mother and the fetus. However, the etiology of PE has not yet been fully understood. Since the imbalance of steroid hormones is associated with the pathogenesis of PE, investigating steroidogenic mechanisms under various PE conditions is essential to understand the entire spectrum of pregnancy disorders. Therefore, the current study established three PE in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A study using next-generation sequencing to detect dysfunctional blastocysts found that decreased expression of CYP11A1 was a cause of embryo implantation failure 17 . Meanwhile, CYP11A1 expression level was significantly higher in PE compared with normal placenta of humans and rats, which is in line with the observed increase in PREG level 18,24 . CYP11A1 overexpression suppressed trophoblast proliferation and induced HTR8/SVneo cell apoptosis by activating caspase-3.…”
Section: Placental Cypsmentioning
confidence: 58%
See 1 more Smart Citation
“…A study using next-generation sequencing to detect dysfunctional blastocysts found that decreased expression of CYP11A1 was a cause of embryo implantation failure 17 . Meanwhile, CYP11A1 expression level was significantly higher in PE compared with normal placenta of humans and rats, which is in line with the observed increase in PREG level 18,24 . CYP11A1 overexpression suppressed trophoblast proliferation and induced HTR8/SVneo cell apoptosis by activating caspase-3.…”
Section: Placental Cypsmentioning
confidence: 58%
“…17 Meanwhile, CYP11A1 expression level was significantly higher in PE compared with normal placenta of humans and rats, which is in line with the observed increase in PREG level. 18,24 CYP11A1 overexpression suppressed trophoblast proliferation and induced HTR8/ SVneo cell apoptosis by activating caspase-3. Similarly, increased placental CYP11A1 expression resulted in the production of lipid peroxides, which may contribute to the pathogenesis of PE.…”
Section: Cyp11a1-associated Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…ALPP, CYP19A1, and FSTL3 were excluded from further analysis as they have been previously reported to be associated with the pathology of PE or FGR. (13)(14)(15)(16)(17)…”
Section: Resultsmentioning
confidence: 99%
“…( 11 ) Microarray analysis has shown that ENDOU mRNA is significantly increased in cytotrophoblasts isolated from PE placentas. ( 12 ) Of these proteins, ALPP, ( 15 ) CYP19A1, ( 14 , 16 ) and FSTL3 ( 13 , 17 ) have already been reported to be associated with the pathology of PE; thus, they were excluded from further investigation. In the present study, the expression levels of APOA1, ENDOU, and MTPN were evaluated in PE-FGR placentas by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…As pregnancy progresses, the placenta becomes the principal source of steroid hormone synthesis [ 8 , 32 ]. An imbalance of steroid hormones is related to many pregnancy complications, such as preeclampsia, caused by insufficient P4 [ 69 ]. A premature increase in P4 levels is related to abnormal implantation and decreased pregnancy rates [ 70 , 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%